EKSPLORASI KAIN GONI MENGGUNAKAN KOMBINASI TEKNIK ANYAM & SULAM - Iko, Dara Salma Tunggal; Puspitasari, Citra; Ramadhan, M. Sigit (Telkom University, 2024)
Jute cloth or also known as burlap cloth is a cloth that existed during the Dutch colonial era. Burlap cloth is made from plant fibers in the form of jute (jute) and rosella (java jute). The use of jute fabric material in the realm of fashion has been widely used in the interior sector and also in the fashion industry. The potential of jute fabric using surface textile techniques can be an attractive alternative design application that can be applied in the development of current fashion products. As time goes by, the use of jute cloth in Indonesia is not only limited to sacks for storing food but is also used as material for fashion products, therefore in this research considering that there is still potential to explore jute cloth using various other techniques, the aim of this research is resulting in a variety of explorations made from jute fabric using a combination of techniques. As for the techniques identified or potential from existing data, it can be seen that jute cloth is still limited as a fabric that is explored using a mixture of several techniques in general. Jute fabric as a material has the potential to be further processed using pre-existing surface textile designs. Keywords: Jute Cloth, Fabric, Combination of Techniques, Fashion.